Mediating effect of job engagement on the relationship between leadership styles and organizational performance - Khan, S.A.; Athifah, N. (University of Jaffna, 2020)
Job engagement has received considerable attention among the academic community and business professionals in recent years. This issue still needs to be prioritized in academic research, especially as it is essential to understand organizational performance's antecedents. The objective of this study is to examine the relationship between leadership styles and organizational performance and explore whether job engagement can mediate this relationship based on social exchange theory. Survey data were collected from the employees working in a mobile phone company in Bangladesh. The collected data were analyzed using SPSS version 21, and Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to test the study hypotheses. The measurement model's result indicates that concerning leadership styles, the relationship between transformational leadership style and organizational performance is statistically significant; whereas, the relationship between transactional and passive-avoidant leadership style with organizational performance is not significant. Similarly, the relationship between transformational leadership style and job engagement is significant; but the relationship between transactional and passive-avoidant leadership style with job engagement is not significant. In terms of mediation effects, job engagement mediates the relationship between leadership styles and organizational performance.
Keywords: Job engagement; Leadership styles and organizational performance